Psychology in Your Life - Grison, Sharah (Norton, 2015)
Psychology in Your Life was created with the realities of the modern classroom in mind–the text and the media (including an interactive ebook) get students actively engaged with the topics, show them how psychology can be relevant to their lives, and teach them how to be critical consumers of information.